Inhibition of mTOR Prevents ROS Production Initiated by Ethidium Bromide-Induced Mitochondrial DNA Depletion - Nacarelli, Timothy; Azar, Ashley; Sell, Christian (Frontiers in Endocrinology, 2014)
The regulation of mitochondrial mass and DNA content involves a complex interaction between mitochondrial DNA replication machinery, functional components of the electron transport chain, selective clearance of mitochondria, and nuclear gene expression. In order to gain insight into cellular responses to mitochondrial stress, we treated human diploid fibroblasts with ethidium bromide at concentrations which induced loss of mitochondrial DNA over a period of 7 days. The decrease in mitochondrial DNA was accompanied by a reduction in steady state levels of the mitochondrial DNA binding protein, TFAM, a reduction in several ETC protein levels, increased mitochondrial and total cellular ROS, and activation of p38 MAPK. However, there was an increase in mitochondrial mass and VDAC levels. In addition, mTOR activity, as judged by p70S6K targets, was decreased while steady state levels of p62/SQSTM1 and parkin were increased. Treatment of cells with rapamycin created a situation in which cells were better able to adapt to the mitochondrial dysfunction, resulting in decreased ROS and increased cell viability but did not prevent the reduction in mitochondrial DNA. These effects may be due to a more efficient flux through the electron transport chain, increased autophagy, or enhanced AKT signaling, coupled with a reduced growth rate. Together, the results suggest that mTOR activity is affected by mitochondrial stress, which may be part of the retrograde signal system required for normal mitochondrial homeostasis.